Quantitative fisheries stock assessment : - Hilborn, Ray (Chapman and Hall, 1992)
Quantitative Fish Stocks Assessment is the first textbook to capture the spirit of the "new fisheries management", in that it is driven by a recognition of the dynamic nature of fish populations and the application of computers and systems analysis to fisheries problems. It contains detailed numerical methods for parameter estimation, confidence bounds, and the formulation of harvesting strategies. The book builds upon the three themes in the subtitle. Choice refers to alternative management actions and alternative models. Dynamics reviews basic concepts of ecology and the interactions between fish and fishermen, as the latter respond to biological variability and to economic opportunity and regulation. Uncertainty describes the all-pervasive feature of fish stocks assessment. This text, written by two highly respected authorities in the field, should also become a standard reference in the area for professionals. It is clearly written at the level accessible to senior undergraduates and is easily understandable without advanced calculus and linear algebra.